2011
DOI: 10.2741/3857
|View full text |Cite
|
Sign up to set email alerts
|

Pulmono-atrial shunt and lung assist to treat right ventricular failure

Abstract: In right ventricular failure (RVF) a decrease of right ventricular afterload and improvement of left atrial filling could be achieved by a pulmonary artery-left atrial (PA)-shunt. To avoid cyanosis, artificial oxygenation is necessary. In 11 pigs a PA-shunt was created. An interventional lung assist device (ILA) was installed from the femoral artery to vein in 5 pigs (serial in relation to native lung: Group I) and into the PA-shunt in 6 pigs (parallel: Group II). RVF was induced by pulmonary artery banding. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 23 publications
(25 reference statements)
1
10
0
Order By: Relevance
“…Τhere is statistical significant difference between groups concerning the percentage change from baseline to 10 minute of the SVR variable and a statistically significant difference between the two groups at 20 minute (p = 0.075). Our recordings of a low MAP and low SVR in both groups are consistent with the results described by other investigators [20-22]. …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Τhere is statistical significant difference between groups concerning the percentage change from baseline to 10 minute of the SVR variable and a statistically significant difference between the two groups at 20 minute (p = 0.075). Our recordings of a low MAP and low SVR in both groups are consistent with the results described by other investigators [20-22]. …”
Section: Discussionsupporting
confidence: 93%
“…Can be easily performed in conjunction with a pumpless lung assist device as Novalung in parallel with the PA shunt or in a serial setting [22]. …”
Section: Discussionmentioning
confidence: 99%
“…This can be accomplished via pulmonary artery-left atrial graft and has been shown to improve RV function. 29,30 Intraoperative echocardiography is used to assess biventricular and valvular function, presence of shunts, and detection of cardiac thrombi. Adequate pump function should be confirmed at this time, and if cardiac index is < 2.0 and central venous pressure is > 20, a temporary RVAD should be considered.…”
Section: Surgical Managementmentioning
confidence: 99%
“…Reverse Potts shunt circulation may be a therapeutic option for patients with systemic or suprasystemic PAH and RV dysfunction . We report the first successful interventional re‐opening of a PDA occluder (ADO I) to establish a reverse Potts shunt circulation in order to treat RV dysfunction refractory to maximal medical treatment.…”
Section: Discussionmentioning
confidence: 99%